Análisis de la demanda eléctrica en la empresa “Molinos Poultier S.A” para determinar la cargabilidad del sistema eléctrico - Lema Vela, Luis Eduardo (2017)
This project was conducted in order to determine the transformers´ degree of chargeability in ‘‘Molinos Poultier S.A'' Company. Therefore, the electrical system of the company is analyzed in transformers which are at the substation in order to improve energy and propose more alternatives to improve the electrical service....